SCANNING ELECTRON-MICROSCOPY OF THE RHODNIUS-NEGLECTUS (HEMIPTERA) LABIAL SALIVARY-GLANDS AFTER STARVATION - Konig, B.; Masuko, T. S.; Rosenberg, B. (Gustav Fischer Verlag, 1993)
Labial salivary glands are found in the majority of insects. They are relatively large, extend back into the thorax, and in Rhodnius, they are cherry red in color due to a pigment derived from traces of hemoglobin absorbed form the gut. In most insects they are acinous shaped, with long excretion channels that present differentiated regions which from salivary reservoirs. The glands may be relatively simple or complexly branched and convoluted. In Rhodnius they are described as being unilobed with no traces of division. The main duct leaves the gland at its anterior extremity. The acini have different kinds of cells but all of them are seen as sources of secretion. Our material has a different shape due to the fact that the animals spent 20 days under starvation conditions. New data are also obtained through treatment with collagenase and HCl. The importance of the study of these glands lies in the fact that it will further understanding of the transmission of Chagas' disease.
Keywords: SALIVARY GLANDS; RHODNIUS; COLLAGENASE; SEM